Brain Death Secondary to Rocky Mountain Spotted Fever Encephalitis. (4th May 2020) - Rhodes, Steven D.; Teagarden, Alicia M.; Graner, Brian; Lutfi, Riad; John, Chandy C.
Abstract : A two-year-old female presented with acutely altered mental status following eight days of fever and rash. She had been camping at an Indiana campground 11 days prior to the onset of illness and was evaluated twice for her fever and rash prior to admission. Laboratory evaluation on admission revealed thrombocytopenia, hyponatremia, and elevated transaminases. The patient developed diffuse cerebral edema, and despite intensive care, the edema led to brain death from Rocky Mountain spotted fever (RMSF). We present this case to highlight the importance of considering RMSF and other tick-borne illnesses in a child with prolonged fever and rash in a nonendemic area and also the difficulty of diagnosis in early stages of disease. A detailed travel history, evaluation of key laboratory findings (white blood count, platelet count, and transaminases), and close follow-up if rash and fevers persist may help to improve detection of RMSF. If a tick-borne illness such as RMSF is suspected, empiric doxycycline therapy should be started immediately, as lab confirmation may take several days and mortality increases greatly after five days of symptoms.